ScalA-PB: Peace, sustainability and agricultural success in your hands - Yomayuza, Karoll Valentina (2024)
From the resurgence of conflicts over scarce resources to the massive displacement of populations due to extreme weather events, the relationship between these phenomena demands innovative and holistic responses. In this dynamic scenario, ScalA-PB emerges, an innovative Android and iOS mobile application designed to comprehensively address the relationship between climate change and agricultural peacebuilding.